Causas y factores de riesgo de baja visión en Latinoamérica: revisión bibliográfica - Pérez Tarazona, María Kamila (Universidad Antonio Nariño, 2021)
Low vision can be defined as an alteration in visual function even after treatment or refractive correction, either glasses or contact lenses (1). Currently, the pathologies that can cause low vision and also cause changes in their quality of life are known (2), therefore, it is relevant to know if these pathologies are equally prevalent in Latin American countries and if the risk factors to which this population is exposed are related to the above. Objective: To analyze the causes and risk factors that lead to low vision in different Latin American countries through a bibliographic review. Results: The main causes of low vision in Latin American countries were cataract, uncorrected refractive error and glaucoma, additionally it was determined that the most prevalent risk factor is sociodemographic. Conclusions: Due to the risk factors present in Latin America, the causes of low vision are cataract and refractive error.